ANTUSIASME PESERTA DIDIK DALAM IMPLEMENTASI GAME BASED LEARNING PADA PEMBELAJARAN BAHASA JAWA TEKS ANEKDOT - Rishanti, Erliyana; Dwijonagoro, Suwarna; Muhajirin, Muhajirin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Javanese plays an important role in preserving local culture, but students' interest in learning it has declined due to external influences. Therefore, teachers need to bring innovative and enjoyable learning methods, such as using the game basic learning model, which encourages active interaction through games. This model allows students to engage interactively in the learning process through gameplay. Along with technological advancements, there are now many educational games that can be used, such as Froggy Jumps and Kahoot. This research was conducted in class XII Multimedia 4 at SMK Wachid Hasyim Surabaya. The purpose of this study is to examine students’ enthusiasm in the implementation of game-based learning in Javanese language lessons, specifically on anecdotal text material. It also aims to motivate students to participate actively in Javanese lessons and encourage other teachers to apply this method in their teaching. The research method used was qualitative, with data collection techniques including observation, interviews, and tests. The results of the study show that many students were enthusiastic and interactive during the lessons. An analysis of the students’ scores in class XII Multimedia 4 revealed an improvement between the pre-test and post-test results. The implementation of game-based learning can enhance students' enthusiasm in learning Javanese, regardless of their backgrounds, as long as the teacher applies the right and innovative methods. ABSTRAK Bahasa Jawa berperan penting dalam melestarikan budaya lokal, namun minat peserta didik terhadap pembelajarannya menurun akibat pengaruh luar. Oleh karena itu, guru perlu menghadirkan inovasi pembelajaran yang menyenangkan, seperti menggunakan model game basic learning yang mendorong interaksi aktif melalui permainan. Pada pembelajaran dengan model tersebut peserta didik diajak untuk menjadi interaktif dalam menerima pelajaran melalui permainan. Diiringi dengan majunya teknologi maka sekarang banyak game edukatif yang bisa digunakan salah satunya froggy jumps dan kahoot. Penelitian ini dilakukan pada kelas XII Multimedia 4 di SMK Wachid Hasyim Surabaya. Tujuan diadakan penelitian ini untuk mengetahui antusiasme peserta didik dalam implementasi game based learning pada pembelajaran Bahasa Jawa materi teks anekdot. Selain itu agar peserta didik semangat dalam mengikuti pembelajaran Bahasa Jawa, serta guru-guru yang lain bisa menerapkan metode ini dalam pembelajaran. Metode penelitian yang digunakan kualitatif dengan teknik pengumpulan data observasi, wawancara, dan test. Hasil dari penelitian ini banyak peserta didik yang antusias serta interaktif pada saat pembelajaran. Analisis nilai peserta didik kelas XII Multimedia 4 pada data yang telah diuji memiliki hasil peningkatan antara pre-test dengan post- test. Penerapan game based learning dapat meningkatkan antusiasme peserta didik dalam pembelajaran Bahasa Jawa, terlepas dari latar belakang mereka, asalkan guru menggunakan metode yang tepat dan inovatif.